Travel politicization facing biopolitics: (Im)mobilities, technological mediations, and identity discourses in collaborative hosting networks for women - Thaís Costa (Via@)
This paper investigates how the biopolitical representation of travelers is affected by political activism on a collaborative hosting network for Black Brazilian women. The context of the neoliberal capitalist economy influences behaviors and the production of subjectivities that are strongly reinforced by technological and media intermediaries, such as platforms and social networks. In the scenario with tourism emerging as a biopolitical phenomenon, traveling bodies are ranked in a market logic with asymmetrical mobility (Sheller, 2017). The methodological course consisted of a literature review, an ethnography of the women's group Couchsurfing das Pretas hosted on Facebook, and a platform analysis to mediate their interactions. The results indicated a tourism politicization from the intense use of digital platforms and the valuation of identities as a biopotency movement against biopolitics discourses.